2017
DOI: 10.1111/apa.13787
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal enuresis impaired children's quality of life and friendships

Abstract: Aim: There have not been any continence-specific measurement tools in Swedish that have allowed clinicians to investigate the quality of life (QoL) in children with bladder dysfunction. This study evaluated the QoL in Swedish children with nocturnal enuresis and tested the reliability of a Swedish translation of the Paediatric Incontinence Questionnaire (PinQ).Methods: This prospective study comprised 46 children aged six to 18 years with nocturnal enuresis, who completed the PinQ after it was translated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
0
20
0
1
Order By: Relevance
“…Children with nocturnal enuresis have impaired self‐esteem, and their impaired quality of life affects their relationships with friends, according to a prospective study by Jönsson Ring et al . The authors based their findings on 46 Swedish children aged six to 18 years with nocturnal enuresis, who completed a translated version of the Paediatric Incontinence Questionnaire.…”
Section: Bedwetting Impaired Children's Quality Of Life and Friendshipsmentioning
confidence: 99%
“…Children with nocturnal enuresis have impaired self‐esteem, and their impaired quality of life affects their relationships with friends, according to a prospective study by Jönsson Ring et al . The authors based their findings on 46 Swedish children aged six to 18 years with nocturnal enuresis, who completed a translated version of the Paediatric Incontinence Questionnaire.…”
Section: Bedwetting Impaired Children's Quality Of Life and Friendshipsmentioning
confidence: 99%
“…Although there is an annual spontaneous cure rate of 15% [ 10 ], living with enuresis often impacts negatively the quality of life of both the child and his parents. On the one hand, Jonsson Ring et al found that children with enuresis have impaired self-esteem that affects their relationships with friends [ 11 ]. On the other hand, Roccella et al revealed that parents of enuretic children show significantly higher stress level than those of typically developing children [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Трудности выявления нарушений МИ неорганического генеза приводят к несвоевременной или неполной их диаг ностике, к низкой эффективности или отсутствию лечения, что сопровождается депривацией и социальной дез адап тацией детей и, как следствие, снижением качества их жизни [3,8,10,11].…”
Section: Introductionunclassified